Досвід роботи комунальної спеціальної воєнізованої аварійно-рятувальної служби "Кобра" м. Запоріжжя - Круглицький, Д. М.; Райко, Валентина Федорівна (Національний технічний університет "Харківський політехнічний інститут", 2023)
Наведено досвід роботи комунальної спеціальної воєнізованої аварійно-рятувальної служби по ліквідації наслідків аварій і надання допомоги постраждалим при надзвичайних ситуаціях.

The work experience of the communal special paramilitary emergency rescue service for eliminating the consequences of accidents and providing assistance to victims in emergency situations is presented.
Work experience of the municipal special military emergency and rescue service "Cobra" in Zaporizhy
Keywords: надзвичайна ситуація; аварійно-рятувальні роботи; управління охороною праці; безпечне виконання робіт; emergency situation; emergency and rescue work; labor protection management; safe performance of work